The Role of Ten-Eleven Translocation Proteins in Inflammation - Gerecke, Christian; Egea Rodrigues, Caue; Homann, Thomas; Kleuser, Burkhard (Frontiers in Immunology, 2022)
Ten-eleven translocation proteins (TET1-3) are dioxygenases that oxidize 5-methyldeoxycytosine, thus taking part in passive and active demethylation. TETs have shown to be involved in immune cell development, affecting from self-renewal of stem cells and lineage commitment to terminal differentiation. In fact, dysfunction of TET proteins have been vastly associated with both myeloid and lymphoid malignancies. Recently, there has been accumulating evidence suggesting that TETs regulate immune cell function during innate and adaptive immune responses, thereby modulating inflammation. In this work, we pursue to review the current and recent evidence on the mechanistic aspects by which TETs regulate immune cell maturation and function. We will also discuss the complex interplay of TET expression and activity by several factors to modulate a multitude of inflammatory processes. Thus, modulating TET enzymes could be a novel pharmacological approach to target inflammation-related diseases and myeloid and lymphoid malignancies, when their activity is dysregulated.